Handling Spirituality/Religion in Professional Training: Experiences of a Sample of Muslim Psychology Students - Patel, Cynthia Joan (Journal of religion and health, 2006)
ABSTRACTWith increasing research interest in the relationship between spirituality/religion and mental health, the present study uses semi-structured interviews on a select group of Muslim students to explore their understanding and handling of spirituality in a secular training programme. Their understanding of spirituality, its perceived role in therapy and their training experiences are subjected to qualitative analysis using the framework approach (Ritchie & Spencer, 1994. In A. Bryman & R.G. Burgess (Eds), Analysing Qualitative Data. London: Routledge). All five participants perceived spirituality as central to human functioning. Probes into their training experience uncovered issues of bias against religious applicants, apprehension about demonstrating religious commitment, fear of punishment for compromising religious integrity, better rapport with Muslim patients but general uncertainty about handling spiritual issues in therapy, and a strong desire for the integration of spirituality/religion in the program.